2004
DOI: 10.1002/ijc.20257
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis and invasive cervical cancer: A pooled analysis of the IARC multicentric case‐control study

Abstract: To determine whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
152
0
17

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 231 publications
(174 citation statements)
references
References 30 publications
5
152
0
17
Order By: Relevance
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding suggests a plausible mechanism whereby C. trachomatis infection could be associated with increased risk for cervical cancer, as has been reported in several epidemiological studies. 7,[10][11][12]23,24 It has been reported that C. trachomatis infection may induce large local amounts of pro-inflammatory chemokines, including IL-1, IL-8 and granulocyte-macrophage colony-stimulating factor 25 producing a chronic inflammatory background that may conceivably contribute to HPV DNA persistence in the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…Chlamydia (C.) trachomatis has been found repeatedly to associate with cervical neoplasia and invasive cancer in cross-sectional case-control studies, 7,8 although the association has commonly been thought to be the result of confounding by HPV. During recent years, an association with C. trachomatis has also been found in several biobank-based longitudinal studies with invasive cervical cancer as endpoint.…”
mentioning
confidence: 99%
“…In contrast, moderate and borderline associations were found with CIN3/CIS. History of CT infection has also been associated with CC in several previous studies [2][3][4]6 and it is assumed it increases the probability that HPV infections will become persistent, increasing thus the risk of neoplasia. 29,30 In contrast, a large prospective study based on the placebo arms of two multinational clinical trials of HPV vaccination found a moderate association between CT PCR positivity and CIN2 but not with CIN3.…”
Section: Epidemiologymentioning
confidence: 99%
“…In addition to HPV, associations have been found with Chlamydia trachomatis (CT) and Human Herpes Virus 2 (HHV-2). [1][2][3][4][5][6] However, most of the evidence comes from retrospective case-control studies and little data are available from prospective designs.…”
mentioning
confidence: 99%
“…The amplified HPV-DNA is identified by sequencing or hybridization with a specific sequence of a DNA or RNA probe. The hybridized DNA-DNA or DNA-RNA complex is then detected by means of colorimetric or chemiluminence techniques [2,14].…”
Section: Introductionmentioning
confidence: 99%